EFFECT OF FREEZING PRESERVATION PERIOD ON SOME SENSORY CHARACTERISTICS OF THREE IRAQI LOCAL FISH SPECIES - Mahmoud, R. A.; Al-Khshali, M. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The current study was conducted to determine the ideal period for freezing of three fish species of in the Iraqi local markets which are common carp  Cyprinus carpio ,catfish Silurus triostegus and mullet Planiliza abu  through sensory evaluation and the effect of freezing time on the flavor, juiciness and general acceptability of fish .A total of20  samples, were taken for each species of fresh local fish and were frozen at 18°C for different freezing periods : 1 day (T2), 15 days (T3), 30 days (T4) and 45 days (T5) , in addition to the fresh treatment T1 that has not been subjected to freezing. Results of common carp showed that the best freezing time was recorded for treatments T2, T3 and T4 which attained 6.8, 6.6 and 6.2, respectively, for the flavor. The treatment T2, T3 and T4 were recorded 6.4, 6.8 and 6.6 respectively, for tenderness .The treatments T2, T3 and T4 were amounted 7.4, 6.6 and 6.6 respectively, for the Juiciness. Results of the general acceptance of treatments T2, T3 and T4 were 7.6, 7.2, 6.6 respectively. Results of the catfish and the mullet for flavor showed that the best freezing period was for the two treatments T2 and T3, which were 7.4, 6.4 in the catfish and 6.6 and 5.4 in the mullet respectively. T2 and T3 continued to be significantly superior to the freshness of the catfish and the mullet  over T4 and T5 and it was 7.0, 6.4 for the catfish and 5.8, 5.6 for the mullet, respectively. T2 and T3 were superior for the juiciness of catfish by 7.0 and 6.6 and for mullet, 5.8 and 5.6 respectively. As for the trait of general acceptance, it was superior in the two treatments T2 and T3 for catfish and mullet  and they were 7.4, 6.8 for catfish 6.8 and 6.4 for mullet respectively.